2003
DOI: 10.1161/01.hyp.0000084874.85653.46
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Multipoint Parametric Linkage Analysis of Pulse Pressure in Large, Extended Utah Pedigrees

Abstract: Abstract-High pulse pressure, a measure of arterial aging, is an important predictor of cardiovascular and general mortality. It has been suggested that the genetic etiology of pulse pressure is the same as systolic blood pressure. We performed a genome-wide, multipoint, parametric linkage analysis in 26 large, extended Utah pedigrees to locate genes affecting pulse pressure. Four parametric models were considered, including dominant and recessive modes of inheritance involving genes for high and low pulse pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 55 publications
4
50
1
2
Order By: Relevance
“…It is surprising that among the three significant linkage peaks, two have been confirmed to show linkage in other populations. In a multipoint linkage scan performed on large and extended Utah pedigrees, Camp et al 31 reported linkage evidence on chromosome 12q at 109 cM, which is covered by our linkage region on chromosome 12 in Figure 1. In another study based on American families, Bielinski et al 13 detected a significant linkage for PP on chromosome 18 at 71 cM; this was the most significant linkage in their study.…”
Section: Discussionmentioning
confidence: 74%
“…It is surprising that among the three significant linkage peaks, two have been confirmed to show linkage in other populations. In a multipoint linkage scan performed on large and extended Utah pedigrees, Camp et al 31 reported linkage evidence on chromosome 12q at 109 cM, which is covered by our linkage region on chromosome 12 in Figure 1. In another study based on American families, Bielinski et al 13 detected a significant linkage for PP on chromosome 18 at 71 cM; this was the most significant linkage in their study.…”
Section: Discussionmentioning
confidence: 74%
“…It is surprising that among the three significant linkage peaks, two have been confirmed to show linkage in other populations. In a multipoint linkage scan performed on large and extended Utah pedigrees, Camp et al (2003) reported linkage evidence on chromosome 12q at 109 cM which is covered by our linkage region on chromosome 12 in Figure 3. In another study based on American families, Bielinski et al (2005) detected a significant linkage for PP on chromosome 18 at 71 cM, the most significant linkage in their study.…”
Section: Figurementioning
confidence: 83%
“…How- ever, in our Utah pedigrees, we did not see evidence for linkage of blood pressure or pulse pressure in this chromosomal region. 10 Logarithm of odds scores were Ͻ0.6 for every marker in the region for SBP, DBP, and pulse pressure. This illustrates that lack of linkage does not rule out significant associations of genes in a particular region with phenotypes of interest.…”
Section: Discussionmentioning
confidence: 99%